Progress towards an eco-friendly insect pest management approach in subtropical agro-ecosystems (South Africa) - Tertia Grové (CABI Agriculture and Bioscience)
Abstract South Africa is a known exporter of subtropical fruit (avocado, litchi and mango). The main production areas for subtropical fruit in South Africa are parts of Limpopo, Mpumalanga and KwaZulu-Natal. The avocado and litchi industries are export orientated while the majority of mangoes produced are processed. The main export markets are the European Union and the United Kingdom. Subtropical fruit production is susceptible to various insect pests that significantly contribute to yield losses. Twenty years ago mainly broad spectrum insecticides (organophosphates and pyrethroids) had been registered for control of pests and progress was made in adopting eco-friendlier management approaches. The lowering of maximum residue levels for pesticides on food products by importing countries provide new challenges for growers. Here, details are provided on the important insect pests of subtropical crops and the current management strategies use for controlling these pests. An integrated pest management strategy should aim to use interventions that lower maximum residue levels. A challenge that still remains is the sucking bug complex on avocado and more environmentally friendly strategies used for suppression need to be developed. An effective trapping system to monitor adult sucking bugs coming into the orchards will be important for effective management. Challenges that still remain are the litchi moth, Cryptophlebia peltastica (Meyrick) (Lepidoptera: Tortricidae) on litchi, and the citrus thrips, Scirtothrips aurantii Faure (Thysanoptera: Thripidae) and the mango seed weevil, Sternochetus mangiferae (Fabricius) (Coleoptera: Curculionidae) on mango. The development and testing of mating disruption products, attract and kill products, and biological control products for litchi moth is important. Biological control products also need to be tested against citrus thrips on mango. The mango industry needs to find more environmentally safe suppression methods that can be used with sanitation to manage mango seed weevil as it is a pest of phytosanitary concern. The set of economic thresholds for the important pests also need some attention. The use of botanical pesticides has not yet been tested on a large scale and could possibly contribute to the control of pests in the future.